STRATEGI PENGEMBANGAN DESTINASI WISATA PANTAI GOSONG DI DESA SUNGAI RAYA KECAMATAN SUNGAI RAYA KEPULAUAN - Gunawan, Dody; Asriati, Nuraini; Christanto, Ludovicus Manditya Hari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the existing conditions, potentials and problems as well as strategies for developing Gosong Beach tourism destinations in Sungai Raya Village, Sungai Raya District, Bengkayang Regency. This research is a descriptive type of research with a qualitative research form. Sources of research data for the Gosong Beach tourist destination in Sungai Raya Village are in the form of documents, archives and other records that reinforce the picture of the situation through visual language. Data collection techniques are observation and interviews. The results of this study are 1) The existing conditions of the Gosong Beach Tourism Destination in Sungai Raya Village in terms of the availability of tourist facilities is very inadequate, such as access roads, signposts, toilets, trash cans, entry counters, security, places of worship, parking areas. 2) The Potential of Gosong Beach Tourism Destinations in Sungai Raya Village offers a variety of panoramic beauty. The specialty of this beach lies in the fine white sand, coconut trees that provide a shady atmosphere, rocky hills. Even though Gosong Beach has an attractive potential, there are several problems that become obstacles in the development and tourist attraction of this destination, 3) Destination Development Strategy Gosong Beach Tourism in Sungai Raya Village It is necessary to add and develop facilities and infrastructure, increase promotion and increase human resources, 4) The first direction of development, namely the SO strategy is to utilize natural and cultural potential to become attractive tourist attractions. The ST strategy is to create attractions/shows from existing potentials such as making landmarks that can become the hallmark of the beach.